The role of basophils in allergy - Falcone, Franco H. (Henry Stewart Talks, 2020)
Human peripheral blood basophils, The basophil count, Basophil growth and development, Surface receptors (chemokine receptors, selectins, integrins), Activation mechanisms (IgE dependent and non-IgE dependent), Surface activation markers and basophil activation tests, The role of basophils in late phase response, Differences between murine and human basophils